2021
DOI: 10.1136/thoraxjnl-2021-216882
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDIA3 in club cells attenuates osteopontin production and lung fibrosis

Abstract: BackgroundThe role of club cells in the pathology of idiopathic pulmonary fibrosis (IPF) is not well understood. Protein disulfide isomerase A3 (PDIA3), an endoplasmic reticulum-based redox chaperone required for the functions of various fibrosis-related proteins; however, the mechanisms of action of PDIA3 in pulmonary fibrosis are not fully elucidated.ObjectivesTo examine the role of club cells and PDIA3 in the pathology of pulmonary fibrosis and the therapeutic potential of inhibition of PDIA3 in lung fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…CD44 functioned as the receptor of SPP1 ( 10 ), which showed a similar expression pattern to SPP1 ( Figure 3B ), and their expressions showed a strong positive correlation ( r = 0.7875, p < 0.0001) ( Figure 3C ). SPP1 is considered a major driver for renal fibrosis ( 11 ), the secretion of which is stimulated by inflammatory cytokines ( 12 ) and the suppression of which could alleviate kidney fibrosis ( 13 ). In our study, the expressions of fibronectin and Col1A1 were gradually elevated in the WBCR and BCR groups compared to those in MCD ( Figures 3E, F ).…”
Section: Resultsmentioning
confidence: 99%
“…CD44 functioned as the receptor of SPP1 ( 10 ), which showed a similar expression pattern to SPP1 ( Figure 3B ), and their expressions showed a strong positive correlation ( r = 0.7875, p < 0.0001) ( Figure 3C ). SPP1 is considered a major driver for renal fibrosis ( 11 ), the secretion of which is stimulated by inflammatory cytokines ( 12 ) and the suppression of which could alleviate kidney fibrosis ( 13 ). In our study, the expressions of fibronectin and Col1A1 were gradually elevated in the WBCR and BCR groups compared to those in MCD ( Figures 3E, F ).…”
Section: Resultsmentioning
confidence: 99%
“…PDIA3 ablation or inhibition resulted in decreases in allergic airway inflammation, airway hyperresponsiveness, peribronchiolar fibrosis, and pulmonary fibrosis. These phenotype improvements were attributed to deficiencies in growth factors (POSTN, EGF, and SPP1), chemoattractant (Eotaxin), and decreases in death receptor, Fas activity [30][31][32][33]. We also observed that PDIA3 depletion decreases influenza-induced apoptosis of lung epithelial cells and disulfide bonds in HA, leading to decrease in influenza burden and airway hyperresponsiveness [3,30].…”
Section: Discussionmentioning
confidence: 67%
“…PDIA3 catalyzes oxidative modifications of numerous proteins, including proteins that are mediators of respiratory diseases [29][30][31][32][33]. PDIA3 ablation or inhibition resulted in decreases in allergic airway inflammation, airway hyperresponsiveness, peribronchiolar fibrosis, and pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific knockout of PDIA3 in B cells inhibits recruitment of MHC class I molecules onto the peptide-loading complex for antigen presentation ( 67 ). PDIA3 is upregulated and secreted by kidney fibroblasts in response to TGFβ1 ( 34 ), is released on platelet activation ( 68 ), and its upregulation has been correlated with pulmonary fibrosis ( 69 ). Cell-surface PDIA3 has also been shown to act with glycosylated calnexin to reduce extracellular disulfide bonds and make ECM more susceptible to degradation by cancer cells ( 39 ).…”
Section: Discussionmentioning
confidence: 99%